2004
DOI: 10.1103/physrevb.70.054519
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field dependence of low-temperature specific heat of the spinel oxide superconductorLiTi2O4

Abstract: Magnetic field dependence of low temperature specific heat of spinel oxide superconductor LiTi 2 O 4 has been elaborately investigated. In the normal state, the obtained electronic coefficient of specific heat ã n = 19.15 mJ/mol K 2 , the Debye temperature È D = 657 K and some other parameters are compared with those reported earlier. The superconducting transition at T c~1 1.4 K is very sharp (∆T c ~ 0.3 K) and the estimated äC/ã n T c is ~1.78. In the superconducting state, the best fit of data leads to the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
23
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 36 publications
6
23
0
Order By: Relevance
“…Third, the temperature dependence of the superconducting energy gap can be fitted well with the BCS theory (Fig. 2d), and the observed 2D 0 /k B T c ¼ 4 (D 0 ¼ 1.93 meV) is consistent with previous reports 6,9 , indicating that LTO is a medium-coupling BCS superconductor. Moreover, a simple relation of 2 , can be used to scale the field-dependent energy gap at different temperatures, for example, T ¼ 2, 6, 10 K (Fig.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…Third, the temperature dependence of the superconducting energy gap can be fitted well with the BCS theory (Fig. 2d), and the observed 2D 0 /k B T c ¼ 4 (D 0 ¼ 1.93 meV) is consistent with previous reports 6,9 , indicating that LTO is a medium-coupling BCS superconductor. Moreover, a simple relation of 2 , can be used to scale the field-dependent energy gap at different temperatures, for example, T ¼ 2, 6, 10 K (Fig.…”
Section: Resultssupporting
confidence: 73%
“…In the Ca 2-x Na x CuO 2 Cl 2 (x ¼ 0.14), the field dependence scales as BlogB, suggested to be an indication of a dirty d-wave superconductor 40 . Previous specific heat experiments have suggested that LTO is an s-wave superconductor 6 . Thus, based on the lack of departure from the linearly dependent ZBC, we conclude that LTO is not likely to be a multiband superconductor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[42,43] This is also backed up by other experimental techniques, such as point contact measurements [44] and specific heat measurements, [45] that clearly point to the existence of s-wave superconductivity. The observed features can however be explained by critical current effects.…”
Section: Distinction Between Critical Current Effects and Multiband Omentioning
confidence: 85%